ENSURING SPEED STABILITY OF THE UNMANNED AERIAL VEHICLE IN DIF-FERENT FLIGHT MODES - Zirka, Andrii; Zirka , Mariia; Kadet , Natalia (Science-based technologies, 2023)
The publication deals with the issue of ensuring the stability of an unmanned aerial vehicle flight by speed. An analysis of the physical essence of the process of ensuring the unmanned aerial vehicle stability by speed is presented. Attention is paid to the flight modes in which the operator (external pilot) may encounter difficulties in the practical piloting of the unmanned aerial vehicle. The possible causes of abnormal situations when flying the unmanned aerial vehicle at speeds close to the borderline low are analyzed. Possible actions of the operator (external pilot) to return the unmanned aerial vehicle to the operating speed range from the area of instability are considered. The article shows the features of stability and controllability of an unmanned aerial vehicle in a route flight mode. Attention is paid to the complexity of piloting and safety of flight in the second modes. The article demonstrates the method of determining the boundary between the first and second flight modes. The features of unmanned aerial vehicle management and ensuring stability in the first and second modes are shown. The issue of dynamic stability of the unmanned aerial vehicle is investigated. Numerical modeling of the longitudinal movement of the unmanned aerial vehicle in free, uncontrolled flight was carried out, trajectories for the unmanned aerial vehicle of the selected configuration with a change in speed and angle of inclination of the trajectory in time were obtained. Graphs of movement trajectories with changes in speed and height over time were constructed, graphs of transient processes were constructed for cases of stable and unstable flight modes. An analysis of the external factors that most affect the flight parameters in various conditions of unmanned aerial vehicle use was carried out.